2022
DOI: 10.1111/age.13235
|View full text |Cite
|
Sign up to set email alerts
|

Genetic basis investigation of wattle phenotype in goat using genome‐wide sequence data

Abstract: In domestic goats, wattles often appear in even numbers, mostly on the neck and a few under the ear. Goat wattle is composed of ectopic cartilage tissue covered by skin and was reported as a dominant inheritance. Thirty‐eight goats from two Southwest Chinese breeds were studied to elucidate the genetic basis of wattle phenotype in goat. Their genomes were sequenced for wide‐genome selective sweep analysis (WGSA) and a genome‐wide association study (GWAS). The WGSA results revealed 500 candidate genes identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…FAN1 and TRPM1 genes were retained in both methods. Among the identified genes, SLC9A9 and NEDD4 genes were previously accounted as a potential candidate gene for wattle presence in goat [42]. Interestingly, our analyses identified both the NEDD4 gene (included in ROH of animals with wattles) and its binding protein N4BP1 (through F ST ), further supporting their potential roles in the development of wattles in goats.…”
Section: Selection Signaturessupporting
confidence: 64%
“…FAN1 and TRPM1 genes were retained in both methods. Among the identified genes, SLC9A9 and NEDD4 genes were previously accounted as a potential candidate gene for wattle presence in goat [42]. Interestingly, our analyses identified both the NEDD4 gene (included in ROH of animals with wattles) and its binding protein N4BP1 (through F ST ), further supporting their potential roles in the development of wattles in goats.…”
Section: Selection Signaturessupporting
confidence: 64%
“…Indeed, a private population's genetic background can severely influence the identification of target-trait-associated markers when a single breed represents the target trait in a GWAS. Accordingly, different associated candidate genomic regions of goat wattle traits were identified from previous reports with various breeds [48,49]. Furthermore, several GWASs on sheep ear size have shown an inconsistently associated candidate genomic region because of the genetic composition of the testing animals [50,51].…”
Section: Resultsmentioning
confidence: 99%
“…First, two genes, namely ATG7 and MAP1LC3A , were found to be associated with the ferroptosis pathway in the LN versus NJ comparison group. Studies have demonstrated that ATG7 is activated by SIRT1 , enhancing chondrocyte autophagy by deacetylating lysine residues to ensure cartilage integrity (Zhang et al., 2022). Additionally, it has been shown that knockdown of ULK1 in goat support cells reduces autophagy activation, as evidenced by reduced expression of the autophagy‐related marker ATG7 (Pang et al., 2019).…”
Section: Discussionmentioning
confidence: 99%